The Relationship between the Oil Prices and Stock Prices: An Application in BIST Chemical, Oil, Plastic Index - Kurtaran Çelik, Melike; Aktaş, Zekiye; Kurtaran, Ahmet; Turan Kurtaran, Ayten (International Journal of Energy Economics and Policy, 2019)
The purpose of this study is to examine the relationship between oil prices and stock prices. The study consists of a daily data set over the period between 03.12.2010 and 06.12.2017. Firstly, the relationship between the variables was measured by the Spearman's rank correlation coefficient. The result of the analysis found that there was a statistically significant negative correlation between oil prices and stock prices, and it was also identified that 15% of the changes in stock price were as result of changes in oil prices. Secondly, in addition to correlation analysis, Augmented Dickey-Fuller and Philipps-Perron unit root test with Engle and Granger cointegration analysis was conducted in order to measure the long term relationship between oil prices and stock prices. As a result of analysis, it was determined that oil and stock prices reached equilibrium in the long run. Keywords: Oil Prices, Stock Prices, Engle Granger Analysis JEL Classifications: Q41, G15, C22 DOI: https://doi.org/10.32479/ijeep.8269